Should Patients with Kearns-Sayre Syndrome and Corneal Endothelial Failure Be Genotyped for a TCF4 Trinucleotide Repeat, Commonly Associated with Fuchs Endothelial Corneal Dystrophy? - Dudakova, Lubica; Skalicka, Pavlina; Davidson, Alice E; Sadan, Amanda N; Chylova, Monika; Jahnova, Helena; Anteneova, Nicole; Tesarova, Marketa; Honzik, Tomas; Liskova, Petra (Genes, 2021)
The aim of this study was to describe the ocular phenotype in a case with Kearns-Sayre syndrome (KSS) spectrum and to determine if corneal endothelial cell dysfunction could be attributed to other known distinct genetic causes. Herein, genomic DNA was extracted from blood and exome sequencing was performed. Non-coding gene regions implicated in corneal endothelial dystrophies were screened by Sanger sequencing. In addition, a repeat expansion situated within an intron of TCF4 (termed CTG18.1) was genotyped using the short tandem repeat assay. The diagnosis of KSS spectrum was based on the presence of ptosis, chronic progressive external ophthalmoplegia, pigmentary retinopathy, hearing loss, and muscle weakness, which were further supported by the detection of ~6.5 kb mtDNA deletion. At the age of 33 years, the proband's best corrected visual acuity was reduced to 0.04 in the right eye and 0.2 in the left eye. Rare ocular findings included marked corneal oedema with central corneal thickness of 824 and 844 µm in the right and left eye, respectively. No pathogenic variants in the genes, which are associated with corneal endothelial dystrophies, were identified. Furthermore, the CTG18.1 genotype was 12/33, which exceeds a previously determined critical threshold for toxic RNA foci appearance in corneal endothelial cells.
Keywords: endothelial failure; Sequence Deletion; mitochondriální DNA; DNA, Mitochondrial; sekvenční delece; fenotyp; Male; Phenotype; corneal dystrophy; Kearnsův-Sayreův syndrom; CTG18.1; Genotype; Cataract; Transcription Factor 4; sekvenování exomu; corneal endothelium; Adult; exome sequencing; dospělí; mužské pohlaví; Endothelium, Corneal; Fuchsova endoteliální dystrofie; Kearns-Sayre syndrome; TCF4; katarakta; rohovkový endotel; transkripční faktor 4; lidé; trinukleotidové repetice; Humans; Fuchs' Endothelial Dystrophy; genotyp; Kearns-Sayre Syndrome; Exome Sequencing; Trinucleotide Repeats